Biomedically relevant chemical constituents of Valeriana officinalis - Patočka, Jiří; Jakl, Jiří (Journal of Applied Biomedicine, 2010)
Valerian is used to treat sleeping disorders, restlessness and anxiety, but it seemsonly to work when taken over long periods (several weeks). Some studies have demonstrated that valerian extracts interact with the GABA and benzodiazepine receptors. Valerian is also used traditionally to treat gastrointestinal pain and spastic colitis. There are no long term safety studies. Valerian contains over 150 chemical constituents and many of them are physiologically active, mainly pyridine alkaloids, some organic acids and terpenes, especially the so called valepotriates, esterified iridoid-monoterpenes. As valepotriates may be potential mutagens, valerian should only be used after consultation with a physician. Valerian medication is sometimes recommended as first line treatment when the benefit-risk relation requires it and is often indicated as transition medication during the discontinuation processes involving bromazepam, clonazepam and diazepam, among others.
Keywords: kyseliny pentanové; Anticonvulsants; analgetika; Animal Experimentation; Plant Extracts; Alkaloids; Humans; alkaloidy; experimenty na zvířatech; hypnotika a sedativa; Analgesics; antikonvulziva; Valerian; Iridoids; Plant Preparations; Hypnotics and Sedatives; lidé; zvířata; anxiolytika; rostlinné extrakty; Anti-Anxiety Agents; iridoidy; Pentanoic Acids; rostlinné přípravky; kozlík (rostlina); Animals; Valerianaceae